Electrochemical device, electronic device and method for preparing negative electrode sheet
By introducing porous dispersant and binder into the negative electrode sheet of the electrochemical device, an appropriate pore structure is formed, and the problems of poor electrolyte infiltration and easy material particles caused by insufficient porosity of the negative electrode sheet are solved, thus achieving high Energy density and excellent cycling performance.
Patent Information
- Application Number
- CN202210345403.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-03-31
AI Technical Summary
After increasing the compaction density of the negative electrode sheet of the existing electrochemical device, the porosity decreases, resulting in poor infiltration of the electrolyte, attenuation of circulation capacity, and easy falloff of material particles, affecting circulation performance.
A porous dispersant is introduced into the negative electrode active material layer of the negative electrode sheet, and the binder is combined to form an appropriate pore structure, improving the electrolyte infiltration and bonding between the material particles.
By increasing the porosity of the negative electrode sheet, the infiltration capacity of the electrolyte is enhanced, the energy density and circulation performance of the electrochemical device are improved, and the adhesion of the negative electrode active material layer is reduced, and the material particles are removed.
Smart Images

Figure BDA0003576351320000111 
Figure BDA0003576351320000121 
Figure BDA0003576351320000122
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical energy storage, and in particular to an electrochemical device, an electronic device and a method for preparing a negative electrode sheet. Background Art
[0002] With the development of electrochemical energy storage technology, higher and higher requirements are placed on the energy density and cycle performance of electrochemical devices (e.g., lithium-ion batteries). In order to improve the energy density of electrochemical devices, the compaction density of the negative electrode sheet tends to increase, but the increase in the compaction density of the negative electrode sheet will lead to a decrease in the porosity of the negative electrode sheet, which is not conducive to the infiltration of the electrolyte, resulting in a decay in the cycle capacity of the electrochemical device. In addition, the formation of a pore structure between the materials in the negative active material layer is not conducive to the bonding between the negative active material particles in the negative active material layer, and it is easy to cause the negative active material particles to fall off as the electrochemical device cycles. Summary of the invention
[0003] The present application provides an electrochemical device, which includes a negative electrode plate, wherein the negative electrode plate includes a negative electrode active material layer, and the negative electrode active material layer includes a negative electrode active material, a porous dispersant, and a binder.
[0004] In some embodiments, the negative electrode active material includes graphite. In some embodiments, the porous dispersant includes at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, carboxymethyl cellulose, lithium hydroxypropyl carboxymethyl cellulose, sodium hydroxypropyl carboxymethyl cellulose, hydroxypropyl carboxymethyl cellulose, lithium hydroxyethyl carboxymethyl cellulose, sodium hydroxyethyl carboxymethyl cellulose or hydroxyethyl carboxymethyl cellulose of a porous structure. In some embodiments, the binder includes at least one of styrene-butadiene rubber, polyacrylic acid, polyacrylic acid salt, polyimide, polyamide-imide, polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, aqueous acrylic resin or polyvinyl formal. In some embodiments, the mass ratio of the negative electrode active material, porous dispersant and binder in the negative electrode active material layer is 96.6-98.6: 0.7-1.7: 0.7-1.7. In some embodiments, the pore size of the pores in the porous dispersant is 50nm to 500nm. In some embodiments, the porosity of the negative electrode active material layer is 25% to 40%.
[0005] An embodiment of the present application further provides an electronic device, comprising the above-mentioned electrochemical device.
[0006] The embodiment of the present application also provides a method for preparing a negative electrode sheet, the method comprising: mixing a negative electrode active material, a dispersant, a pore former and a binder with deionized water in a preset ratio to obtain a negative electrode slurry; forming the negative electrode slurry on a negative electrode current collector, drying, so that the pore former volatilizes, and obtaining a negative electrode sheet. In some embodiments, the pore former includes at least one of N-methylpyrrolidone, dimethylacetamide, dimethylformamide or dimethyl sulfoxide. In some embodiments, the boiling point of the pore former is higher than that of water by more than 40°C.
[0007] In some embodiments, the mass ratio of the negative electrode active material, the dispersant, the pore former and the binder is 96.6-98.6: 0.7-1.7: 0.01-0.3: 0.7-1.7. In some embodiments, the negative electrode active material includes graphite. In some embodiments, in some embodiments, the dispersant includes at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, carboxymethyl cellulose, lithium hydroxypropyl carboxymethyl cellulose, sodium hydroxypropyl carboxymethyl cellulose, hydroxypropyl carboxymethyl cellulose, lithium hydroxyethyl carboxymethyl cellulose, sodium hydroxyethyl carboxymethyl cellulose or hydroxyethyl carboxymethyl cellulose. In some embodiments, the binder includes at least one of styrene-butadiene rubber, polyacrylic acid, polyacrylic acid salt, polyimide, polyamide-imide, polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, water-based acrylic resin or polyvinyl formal.
[0008] The present application uses a porous dispersant in the negative electrode plate to improve the infiltration of the electrolyte in the negative electrode plate, thereby improving the cycle performance of the electrochemical device while obtaining a high energy density, and can improve the bonding between the negative electrode active materials in the negative electrode active material layer relative to the pores not formed in the negative electrode active material layer by the porous dispersant. DETAILED DESCRIPTION
[0009] The following embodiments may enable those skilled in the art to more fully understand the present application, but do not limit the present application in any way.
[0010] In order to improve the porosity of the negative electrode sheet, there are usually the following methods: mold pore making, using a mold with a fixed shape and position to needle-puncture the surface of the negative electrode sheet to form multiple pores; sintering pore making, using a high-temperature treatment process to decompose the binder in the negative electrode sheet to form multiple pores; laser pore making, using a laser to convert light energy into heat energy, so that the binder in the negative electrode sheet is decomposed to form multiple pores. However, mold pore making requires additional equipment investment, additional processes, and reduced production efficiency, and requires a fixed negative electrode sheet size, lacks flexibility, and expensive molds; sintering pore making also requires additional equipment investment, additional processes, reduced production efficiency, and high energy consumption, which is not conducive to environmental protection; laser pore making also requires additional equipment investment, additional processes, reduced production efficiency, and high energy consumption, which is not conducive to environmental protection.
[0011] Generally, a pore-forming agent can be used to form pores in the negative electrode active material layer to improve the infiltration of the electrolyte in the negative electrode active material layer. However, since a pore structure is formed between the materials in the negative electrode active material layer, it is not conducive to the bonding between the negative electrode active material particles in the negative electrode active material layer. As the electrochemical device is cycled, it is easy to cause the negative electrode active material particles to fall off, for example, causing the surface layer of the negative electrode active material layer to fall off, so that the surface layer of the negative electrode active material layer with a pore structure is lost, affecting the cycle performance of the electrochemical device.
[0012] Some embodiments of the present application provide an electrochemical device, the electrochemical device comprising a negative electrode sheet. In some embodiments, the negative electrode sheet comprises a negative electrode active material layer. In some embodiments, the negative electrode active material layer comprises a negative electrode active material, a porous dispersant and a binder. In some embodiments, the negative electrode active material can be used for the insertion and extraction of lithium ions, the dispersant is conducive to the dispersion of the slurry during the preparation of the negative electrode sheet, and the binder is used for the bonding of the material components in the negative electrode active material layer to form a stable negative electrode active material layer.
[0013] By using a porous dispersant, the porosity of the negative electrode sheet can be increased, the infiltration of the electrolyte in the negative electrode sheet can be improved, and the cycle performance of the electrochemical device can be improved while obtaining a high energy density. In addition, compared with the pores not formed in the negative electrode active material layer, the pore structure in the dispersant does not basically affect the bonding between the negative electrode active materials, thereby improving the bonding between the negative electrode active materials in the negative electrode active material layer, thereby improving the cycle performance of the electrochemical device.
[0014] In some embodiments, the negative electrode active material includes graphite. In some embodiments, the negative electrode active material layer may also include a silicon-based material. In some embodiments, the silicon-based material includes at least one of silicon, silicon-oxygen material, silicon-carbon material, or silicon-oxygen-carbon material.
[0015] In some embodiments, the porous dispersant includes at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, carboxymethyl cellulose, lithium hydroxypropyl carboxymethyl cellulose, sodium hydroxypropyl carboxymethyl cellulose, hydroxypropyl carboxymethyl cellulose, lithium hydroxyethyl carboxymethyl cellulose, sodium hydroxyethyl carboxymethyl cellulose, or hydroxyethyl carboxymethyl cellulose having a porous structure. The dispersant and the pore former can form a two-phase structure with the dispersant as a continuous phase and the pore former as a dispersed phase, and a porous dispersant is formed after the pore former evaporates.
[0016] In some embodiments, the binder includes at least one of styrene-butadiene rubber, polyacrylic acid, polyacrylic acid salt, polyimide, polyamide-imide, polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, aqueous acrylic resin or polyvinyl formal. In some embodiments, the mass ratio of the negative electrode active material, porous dispersant and binder in the negative electrode active material layer is 96.6-98.6:0.7-1.7:0.7-1.7. In some embodiments, if the mass content of the dispersant in the negative electrode active material layer is too small, it is not conducive to the uniform dispersion of the slurry; if the mass content of the dispersant in the negative electrode active material layer is too large, it will adversely affect the energy density of the electrochemical device.
[0017] In some embodiments, the pores in the porous dispersant have a pore size of 50 nm to 500 nm. In some embodiments, the pore size of the pores in the porous dispersant can be measured, for example, by electron microscopy. In some embodiments, the pore depth of the pores is 5 nm to 500 nm. In some embodiments, the shape of the pores is circular, elliptical, semicircular or irregular. In some embodiments, the porosity of the negative electrode active material layer is 25% to 40%. If the porosity of the negative electrode active material layer is too small, it is not conducive to the infiltration of the electrolyte, thereby affecting the cycle performance of the electrochemical device; if the porosity of the negative electrode active material layer is too large, it is not conducive to the improvement of the energy density of the electrochemical device.
[0018] In some embodiments, the present application also provides a method for preparing a corresponding negative electrode sheet, the method comprising: mixing a negative electrode active material, a dispersant, a pore former and a binder with deionized water in a preset ratio to obtain a negative electrode slurry. In some embodiments, the types and corresponding mass ratios of the negative electrode active material, dispersant and binder are as described above and are not repeated here. In some embodiments, the mass ratio of the negative electrode active material, dispersant, pore former and binder is 96.6-98.6: 0.7-1.7: 0.01-0.3: 0.7-1.7. In some embodiments, the method further comprises: forming the negative electrode slurry on the negative electrode current collector, drying, volatilizing the pore former, and obtaining a negative electrode sheet. In some embodiments, the negative electrode slurry can be formed on the negative electrode current collector by coating.
[0019] In some embodiments, the pore former includes at least one of N-methylpyrrolidone (NMP), dimethylacetamide (DMAC), dimethylformamide (DMF) or dimethyl sulfoxide (DMSO). In some embodiments, the boiling point of the pore former is higher than the boiling point of water by more than 40°C, further, more than 50°C, further, the boiling point of the pore former is between 150°C and 300°C, further, the boiling point of the pore former is between 150°C and 230°C. In this way, during the drying or drying process, the water in the negative electrode active material layer can evaporate first, and then these pore formers can form a two-phase structure with the dispersant as the continuous phase and the pore former as the dispersed phase with the dispersant. When the pore former volatilizes or evaporates, the dispersant forms a porous structure, that is, a porous dispersant. If the boiling point of the pore former is close to that of water, for example, the boiling point of the pore former is 120°C, then the boiling point of the mixture of the pore former and water may be lower than 100°C. When the water evaporates, most of the pore former has also evaporated, and thus the two-phase structure described above with the dispersant as the continuous phase and the pore former as the dispersed phase cannot be formed, and thus no porous dispersant can be obtained. The formed porous dispersant is conducive to the rapid diffusion of the electrolyte in the negative electrode sheet, accelerates the migration speed of lithium ions, helps to reduce the concentration polarization generated during rapid charge and discharge, and improves the electrochemical performance of the electrochemical device.
[0020] In some embodiments, the pore former is a non-alcohol pore former. Alcohol pore formers easily form a blend with the dispersant. A small amount of alcohol pore former blended with the local dispersant is not conducive to the formation of uniform pores in the porous dispersant and easily causes local collapse of the dispersant.
[0021] In some embodiments, the dispersant includes at least one of sodium carboxymethylcellulose, lithium carboxymethylcellulose, carboxymethyl cellulose, lithium hydroxypropyl carboxymethyl cellulose, sodium hydroxypropyl carboxymethyl cellulose, hydroxypropyl carboxymethyl cellulose, lithium hydroxyethyl carboxymethyl cellulose, sodium hydroxyethyl carboxymethyl cellulose, or hydroxyethyl carboxymethyl cellulose. In some embodiments, the binder includes at least one of styrene-butadiene rubber, polyacrylic acid, polyacrylic acid salt, polyimide, polyamide-imide, polyvinylidene fluoride, polyvinyl difluoride, polytetrafluoroethylene, water-based acrylic resin, or polyvinyl formal.
[0022] In some embodiments of the present application, a negative electrode plate including a porous dispersant is prepared by adopting a non-solvent evaporation method, a pore former (non-alcohol solvent) is added to the dispersant solution, slurry coating is performed, and then drying is performed. The boiling point of the pore former is higher than that of water, and the water evaporates first. After the water evaporates, the pore former droplets are distributed in the film formed by the dispersant, forming a two-phase structure with the dispersant as the continuous phase and the pore former as the dispersed phase. Subsequently, the temperature continues to rise, the pore former evaporates, and becomes the source of pores, thereby forming a negative electrode plate including a porous dispersant.
[0023] In some embodiments, the negative electrode plate may further include a negative electrode current collector, and the negative electrode active material layer is located on one side or both sides of the negative electrode current collector. In some embodiments, the negative electrode current collector may be at least one of copper foil, nickel foil or carbon-based current collector. In some embodiments, the bonding force between the negative electrode active material layer and the negative electrode current collector is 8N / m to 20N / m. In some embodiments, the bonding force between the negative electrode active material layer and the negative electrode current collector is tested under the following conditions: the coating amount is 80mg / 1540.25mm 2 Up to 200mg / 1540.25mm 2 , compacted density is 1.40g / cm 3 Up to 1.80g / cm 3 In some embodiments, the ionic conductivity of the negative electrode active material layer is 0.1 S / cm to 0.4 S / cm. If the ionic conductivity of the negative electrode active material layer is too small, it will affect the kinetic performance of the electrochemical device; if the ionic conductivity of the negative electrode active material layer is too large, the ionic conductivity of the negative electrode active material layer is too high, which will greatly increase the material cost.
[0024] In some embodiments, the electrochemical device includes an electrode assembly, which may include a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet. In some embodiments, the positive electrode sheet includes a positive current collector and a positive active material layer. In some embodiments, the positive active material layer may be disposed on one or both sides of the positive current collector.
[0025] In some embodiments, the positive electrode current collector may be aluminum foil, and of course, other positive electrode current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive electrode current collector may be 1 μm to 50 μm. In some embodiments, the positive electrode active material layer may be coated only on a partial area of the positive electrode current collector.
[0026] In some embodiments, the positive electrode active material layer may include a positive electrode active material, a conductive agent and a binder. In some embodiments, the positive electrode active material may include at least one of lithium cobaltate, lithium iron phosphate, lithium aluminum oxide, lithium manganate or nickel cobalt manganate. In some embodiments, the conductive agent of the positive electrode plate may include at least one of conductive carbon black, lamellar graphite, graphene or carbon nanotubes. In some embodiments, the binder in the positive electrode plate may include polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, a styrene-acrylate copolymer, a styrene-butadiene copolymer, a polyamide, a polyacrylonitrile, a polyacrylate, a polyacrylic acid, a polyacrylate, a carboxymethyl cellulose sodium, polyvinyl acetate, polyvinylpyrrolidone, a polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. In some embodiments, the mass ratio of the positive active material, the conductive agent and the binder in the positive electrode active material layer is (80-99): (0.1-10): (0.1-10), but this is only an example, and any other suitable mass ratio may be used.
[0027] In some embodiments, the separator includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the stability of the battery through the shutdown effect. In some embodiments, the thickness of the separator is in the range of about 3 μm to 20 μm.
[0028] In some embodiments, the surface of the isolation membrane may further include a porous layer, the porous layer being disposed on at least one surface of the isolation membrane, the porous layer including inorganic particles and a binder, the inorganic particles being selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. In some embodiments, the pores of the isolation membrane have a diameter in the range of about 0.01 μm to 1 μm. The binder of the porous layer is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The porous layer on the surface of the separator can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the separator, and enhance the adhesion between the separator and the pole piece.
[0029] In some embodiments, the electrochemical device includes a lithium ion battery, but the present application is not limited thereto. In some embodiments, the electrochemical device also includes an electrolyte, and the electrolyte includes at least one of a fluoroether, a fluoroethylene carbonate, or an ether nitrile. In some embodiments, the electrolyte also includes a lithium salt, and the lithium salt includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate, and the concentration of the lithium salt is 1 mol / L to 2 mol / L, and the mass ratio of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate is 0.06 to 5. In some embodiments, the electrolyte may also include a non-aqueous solvent. The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents, or a combination thereof.
[0030] The carbonate compound may be a linear carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.
[0031] Examples of chain carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or combinations thereof.
[0032] Examples of the carboxylic acid ester compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.
[0033] Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.
[0034] Examples of other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphoric acid esters or combinations thereof.
[0035] Embodiments of the present application also provide an electronic device including the above-mentioned electrochemical device. The electronic device of the embodiment of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a drone, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0036] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example.
[0037] Comparative Example 1
[0038] Preparation of negative electrode sheet: The current collector uses copper foil, the negative electrode active material uses artificial graphite, the binder uses styrene-butadiene rubber, and the dispersant uses sodium carboxymethyl cellulose. Artificial graphite, styrene-butadiene rubber, and sodium carboxymethyl cellulose are mixed in a mass percentage ratio of 97.4:1.3:1.3 and dispersed in deionized water to form a slurry. After stirring evenly, it is coated on the copper foil and dried to form a negative electrode active material layer. After cold pressing and stripping, the negative electrode sheet is obtained. Among them, the coating amount of the negative electrode active material layer is 150mg / 1540.25mm 2 , compacted density is 1.74g / cm 3 .
[0039] Preparation of positive electrode sheet: The positive electrode active material lithium cobalt oxide, conductive carbon black, and binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in an N-methylpyrrolidone solvent system at a mass percentage ratio of 94.8:2.8:2.4, and then coated on aluminum foil to obtain a positive electrode active material layer with a thickness of 80μm. After drying and cold pressing, a positive electrode sheet was obtained.
[0040] Preparation of isolation film: polyacrylate is stirred to form a uniform slurry, the slurry is coated on both sides of the porous substrate (polyethylene), and the isolation film is formed after drying.
[0041] Preparation of electrolyte: In an environment with a water content of less than 10 ppm, lithium hexafluorophosphate and a non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC) = 20:30:20:28:2, mass percentage ratio) are prepared in a mass percentage ratio of 8:92 to form an electrolyte with a lithium salt concentration of 1 mol / L.
[0042] Preparation of lithium-ion battery: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain the electrode assembly. Place the electrode assembly in the outer packaging aluminum plastic film, remove moisture at 80°C, inject the above electrolyte and package, and obtain the lithium-ion battery through the process of formation, degassing, shaping, etc.
[0043] In Comparative Examples 2 to 11, only the preparation of the negative electrode sheets is different from that in Comparative Example 1, specifically, the content ratio of each component of the negative electrode active material layer, the coating amount or the compaction density is different.
[0044] The only difference between Example 1 and Comparative Example 1 is the preparation of the negative electrode sheet, specifically, a pore-forming agent dimethylformamide (DMF) with a mass content of 0.015% is added to the slurry of the negative active material layer. The difference between Examples 2 to 5 and Example 1 is that the amount of pore-forming agent DMF added is different. The difference between Examples 6 to 8 and Comparative Examples 12 to 13 and Example 3 is that the types of pore-forming agents used are different, wherein the pore-forming agents in Comparative Examples 12 to 13 can form a pore structure between the materials of the negative active material layer. The difference between Examples 9 to 11 and Example 3 is that the compaction density of the negative active material layer is different. The difference between Examples 12 to 15 and Example 3 is that the coating amount of the negative active material layer is different. The difference between Examples 16 to 23 and Example 3 is that the types of dispersants used are different. The difference between Examples 24 to 26 and Example 3 is that the contents of the components of the negative active material layer are different.
[0045] In addition, in the present application, the following method can be used to measure the corresponding parameters.
[0046] 1) Adhesion test between negative electrode active material layer and negative electrode current collector: The brand of the instrument used for the adhesion test between the negative electrode active material layer and the negative electrode current collector is Instron, model 33652. Take a negative electrode sheet (width 30 mm × length (100 mm to 160 mm)), fix it on a steel plate with double-sided adhesive tape (model: 3M9448A, width 20 mm × length (90 mm to 150 mm)), fix a paper tape with the same width as the negative electrode sheet to one side of the negative electrode sheet with adhesive tape, adjust the limit block of the tensile testing machine to a suitable position, fold the paper tape upward and slide 40 mm, the sliding rate is 50 mm / min, and test the adhesion between the negative electrode active material layer and the negative electrode current collector at 180° (i.e., stretching in the opposite direction).
[0047] 2) Test of compaction density of negative electrode active material layer:
[0048] Take a fully discharged lithium-ion battery, disassemble the negative electrode sheet, clean it, dry it, and use an electronic balance to weigh a certain area S of the negative electrode sheet (the negative electrode current collector is coated with a negative electrode active material layer on both sides), and record the weight as W1. Use a micrometer to measure the thickness T1 of the negative electrode sheet. Use a solvent to wash off the negative electrode active material layer, dry it, measure the weight of the negative electrode current collector, record it as W2, and use a micrometer to measure the thickness T2 of the negative electrode current collector. Calculate the weight W0 and thickness T0 of the negative electrode active material layer set on one side of the negative electrode current collector and the compaction density of the negative electrode active material layer by the following formula:
[0049] W0=(W1-W2) / 2
[0050] T0=(T1-T2) / 2
[0051] The compaction density of the negative electrode active material layer = W0 / (T0×S).
[0052] 3) Porosity test of negative electrode active material layer: The porosity of the negative electrode active material layer was tested by gas replacement method: more than 50 negative electrode sheets with a radius of d were punched out using the same mold, and the thickness h of each negative electrode active material layer was measured (as described in 2, which is the thickness of the negative electrode sheet minus the thickness of the negative electrode collector divided by 2), and loaded into the sample cup of the true density tester (AccuPycⅡ1340), and the negative electrode active material layer was filled with He in the closed sample chamber, thereby measuring the true volume V of the negative electrode active material layer, and finally the porosity P of the negative electrode active material layer was obtained by the following formula: P = (1-V / πd 2 ×50×h)×100%.
[0053] 4) Negative electrode wettability test: The wettability of the negative electrode is reflected in its ability to absorb electrolyte and the amount of electrolyte absorbed per unit time.
[0054] Compare the absorption speed of the same amount of electrolyte by different negative electrode plates of the same weight. The negative electrode plate that absorbs the electrolyte first has a strong absorption capacity. Add 20μg of electrolyte to the negative electrode plate to test its corresponding wetting time. The plate with a short wetting time has a strong wettability.
[0055] The absorption and storage capacity of electrolyte by different negative electrode sheets of the same weight immersed in electrolyte was compared. The negative electrode sheets were taken out at the same time after soaking for the same time. The heavier negative electrode sheets had stronger absorption capacity. 5.0g of negative electrode sheets were taken respectively and immersed in electrolyte to test the electrolyte absorption capacity. The negative electrode sheets with high electrolyte absorption capacity had strong wettability.
[0056] 5) Ionic conductivity of the negative electrode active material layer: Bake the lithium-ion battery at 60°C for 4 hours before use; prepare a die cutter, 23mm*35mm*2mm; use ceramic scissors to cut the produced negative electrode sheet into small pieces larger than the size of the die cutter and place them on the die cutter for punching. Use tweezers to take out the charged negative electrode sheet for later use. Then make the negative electrode sheet into a single-layer symmetrical battery; place the symmetrical battery in an electrochemical workstation to test EIS, set the frequency to 0.5Hz~200kHz, and the perturbation voltage to 10mV; calculate the ionic resistance Rion of the negative electrode sheet through the intersection of two straight lines in the electrochemical impedance spectroscopy (EIS);
[0057] Ionic conductivity = Rion*A (negative electrode sheet area) / d (negative electrode sheet thickness).
[0058] 6) Test method for capacity retention after cycling:
[0059] At 45°C, the lithium-ion battery is charged to 4.45V at a constant current of 1C, then charged to a current of 0.05C at a constant voltage, and then discharged to 3.0V at a constant current of 1C. This is the first cycle. The lithium-ion battery is cycled 400 times and 800 times under the above conditions. The capacity retention rate of the lithium-ion battery after cycling is calculated by the following formula:
[0060] Capacity retention rate after cycle = (discharge capacity corresponding to the number of cycles / discharge capacity of the first cycle) × 100%.
[0061] 7) Test method for discharge percentage:
[0062] At 25°C, charge at 0.5C constant current to 4.45V, charge at constant voltage to 0.05C cut-off, then discharge at 0.5C constant current to 3.0V cut-off, record as 25°C discharge capacity. At 25°C, charge at 0.5C constant current to 4.45V, charge at constant voltage to 0.05C cut-off, then place the lithium-ion battery in a -20°C constant temperature box, let stand for 2 hours, then discharge at 0.5C constant current to 3.0V cut-off, record as -20°C discharge capacity. Calculate the discharge percentage of lithium-ion batteries by the following formula:
[0063] Discharge percentage = (-20°C discharge capacity / 25°C discharge capacity) × 100%.
[0064] Tables 1 and 2 show various parameters and evaluation results of Examples 1 to 26 and Comparative Examples 1 to 13.
[0065] Table 1
[0066]
[0067]
[0068] Table 2
[0069]
[0070]
[0071]
[0072] By comparing Example 1 and Comparative Example 1, it can be seen that when preparing the negative electrode sheet, by using even a small amount of pore-forming agent to form a porous dispersant, the porosity of the negative electrode active material layer can be increased, the amount of electrolyte infiltration can be improved, the ion conductivity and discharge percentage of the negative electrode active material layer can be increased, and the cycle capacity retention rate of the lithium ion battery can be improved. In addition, while the porous dispersant increases the porosity of the negative electrode active material layer, the bonding force of the negative electrode sheet is almost not lost.
[0073] In Examples 1 to 5, as the amount of pore former increases, the porosity of the negative electrode active material layer first increases and then decreases. This is because when the amount of pore former is small, the number of pores formed is small. As the amount of pore former increases, the pore former agglomerates to form macropores, the dispersant agglomerates and settles, and the number of effective pores formed decreases. In Example 5, due to poor agglomeration and dispersion of the dispersant, the bonding force between the negative electrode active material layer and the negative electrode current collector decreases by 2N / m. Therefore, the amount of pore former is preferably 0.01% to 0.3%, and the amount in Example 3 is the best. At this time, the pore distribution of the porous dispersant is evenly distributed, and the pore size is 50-500nm, which does not cause a reduction in effective bonding sites, does not deteriorate the bonding force, and has the highest porosity. The corresponding negative electrode sheet wettability is also the best, the ionic conductivity is the highest, and the low-temperature discharge percentage of the assembled lithium-ion battery is also the highest.
[0074] In Examples 6 to 8, different types of pore-forming agents were used to obtain negative electrode sheets with high porosity, excellent wettability of the negative electrode sheets, improved ion conductivity, increased discharge percentage, and improved cycle capacity retention.
[0075] By comparing comparative examples 1 to 4 and embodiments 3 and embodiments 9 to 11, it can be seen that for different compaction densities, after the pore-forming agent is used to form a porous dispersant, the porosity of the negative electrode plate is significantly increased compared with the corresponding comparative examples, the wettability of the negative electrode plate is enhanced, the ionic conductivity and discharge percentage are significantly improved, and the cycle capacity retention rate is improved.
[0076] By comparing comparative examples 5 to 8 and embodiments 12 to 15, it can be seen that for different coating amounts of the negative electrode active material layer, after the pore-forming agent is used to form a porous dispersant, the porosity of the negative electrode plate is significantly increased compared with the comparative examples, the wettability of the negative electrode plate is enhanced, the ionic conductivity and the discharge percentage are significantly improved, and the cycle capacity retention rate is improved.
[0077] In Examples 16 to 23, different types of dispersants were used to obtain negative electrode sheets with high porosity and high wettability, and the ionic conductivity and discharge percentage were significantly improved, and the cycle capacity retention rate was improved.
[0078] By comparing comparative examples 9 to 11 and embodiments 24 to 26, it can be seen that the use of dispersants with different mass contents in the negative electrode active material layer can improve the porosity of the negative electrode plate, and the wettability is significantly improved, the ionic conductivity and discharge percentage are both improved, and the cycle capacity retention rate of the lithium-ion battery is improved.
[0079] By comparing Examples 6 to 8 and Comparative Examples 12 to 13, it can be seen that by forming a porous dispersant, rather than forming a pore structure between the materials in the negative electrode active material layer as in Comparative Examples 12 to 13 (using acetone and tetrahydrofuran as pore formers, respectively), the bonding force of the negative electrode sheet can be improved, thereby improving the capacity retention rate after 800 cycles. This is because the formation of a pore structure between the materials in the negative electrode active material layer is not conducive to the bonding between the negative electrode active material particles in the negative electrode active material layer. As the electrochemical device cycles (for example, after more than 600 cycles), it is easy to cause the negative electrode active material particles to fall off, for example, causing the surface layer of the negative electrode active material layer to fall off, causing the negative electrode active material layer with a pore structure to be lost, affecting the cycle capacity retention rate of the electrochemical device.
[0080] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of disclosure involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features. For example, the above features are replaced with the technical features with similar functions disclosed in the present application.
Claims
1. An electrochemical device comprising: A negative electrode sheet, the negative electrode sheet comprising a negative electrode active material layer, the negative electrode active material layer comprising a negative electrode active material, a porous dispersant and a binder; Wherein, the negative electrode sheet is prepared by the following steps: The negative electrode active material, the dispersant, the pore former and the binder are mixed with deionized water in a preset ratio to obtain a negative electrode slurry; Forming the negative electrode slurry on the negative electrode current collector, and drying to volatilize the pore-forming agent, thereby obtaining the negative electrode sheet; Wherein, the pore-forming agent includes at least one of N-methylpyrrolidone, dimethylacetamide, dimethylformamide or dimethyl sulfoxide, and the mass ratio of the negative electrode active material, the dispersant, the pore-forming agent and the binder is 96.6-98.6:0.7-1.7:0.01-0.3:0.7-1.7; the dispersant includes at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, carboxymethyl cellulose, lithium hydroxypropyl carboxymethyl cellulose, sodium hydroxypropyl carboxymethyl cellulose, hydroxypropyl carboxymethyl cellulose, lithium hydroxyethyl carboxymethyl cellulose, sodium hydroxyethyl carboxymethyl cellulose or hydroxyethyl carboxymethyl cellulose.
2. The electrochemical device according to claim 1, wherein: The negative electrode active material includes graphite.
3. The electrochemical device according to claim 1, wherein The binder includes at least one of styrene-butadiene rubber, polyacrylic acid, polyacrylic acid salt, polyimide, polyamide-imide, polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, water-based acrylic resin or polyvinyl formal.
4. The electrochemical device according to claim 1, wherein The pores in the porous dispersant have a pore diameter of 50 nm to 500 nm.
5. The electrochemical device according to claim 1, wherein The negative electrode active material layer has a porosity of 25% to 40%.
6. An electronic device comprising the electrochemical device according to any one of claims 1 to 5.
7. A method for preparing the negative electrode sheet according to claim 1, comprising: Mixing the negative electrode active material, the dispersant, the pore former and the binder with deionized water in a preset ratio to obtain a negative electrode slurry; Forming the negative electrode slurry on the negative electrode current collector, and drying to volatilize the pore-forming agent, thereby obtaining the negative electrode sheet; Wherein, the pore-forming agent includes at least one of N-methylpyrrolidone, dimethylacetamide, dimethylformamide or dimethyl sulfoxide, and the boiling point of the pore-forming agent is higher than that of water by more than 40°C; The mass ratio of the negative electrode active material, the dispersant, the pore former and the binder is 96.6-98.6:0.7-1.7:0.01-0.3:0.7-1.7; the dispersant includes at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, carboxymethyl cellulose, lithium hydroxypropyl carboxymethyl cellulose, sodium hydroxypropyl carboxymethyl cellulose, hydroxypropyl carboxymethyl cellulose, lithium hydroxyethyl carboxymethyl cellulose, sodium hydroxyethyl carboxymethyl cellulose or hydroxyethyl carboxymethyl cellulose.
8. The method according to claim 7, wherein: At least one of the following is met: The negative electrode active material includes graphite; The binder includes at least one of styrene-butadiene rubber, polyacrylic acid, polyacrylic acid salt, polyimide, polyamide-imide, polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, water-based acrylic resin or polyvinyl formal.
Citation Information
Patent Citations
Negative pole piece, preparing method thereof and lithium ion battery
CN105206798A
All-solid lithium ion battery with porous gradient structure and preparation method thereof
CN110350238A